1998
DOI: 10.1021/ma980914u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Long Chain Branching in Continuous Solution Polymerization of Ethylene Using Constrained Geometry Metallocene

Abstract: Our high-temperature and high-pressure continuous stirred-tank reactor (CSTR) has been used for the polymerization of ethylene with the constrained geometry metallocene system, [C5-Me4(SiMe2N t Bu)]TiMe2 (CGC-Ti)/ tris(pentafluorophenyl)boron (TPFPB)/ modified methylaluminoxane (MMAO), in Isopar E solution at 500 psig. Polyethylenes (PE) with long chain branching (LCB) densities up to 0.44 carbons/10 000 carbons, melt flow index ratios of 7.4-25.7, and narrow polydispersity indexes about 2 were synthesized. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(174 citation statements)
references
References 15 publications
6
167
1
Order By: Relevance
“…The discrepancy between the shear thinning behavior of the aliphatic polyesters and that of the ethylene copolymers comes from the fact that longchain branches were formed by the CGCT catalyzed copolymerization of ethylene and 1-octene with the in situ-produced vinyl terminated polyethylene, due to the chain termination by ␤-hydride elimination and/or transfer to monomers, because long-chain branched polymers have higher shear sensitivity compared to the linear counterparts. Wang et al 13 observed long-chain branches up to 0.44/10,000 carbons were formed during ethylene homopolymerization with CGCT in a continuous stirred-tank reactor operating at 35 atm and 140 -190°C. Figure 6 are cole-cole plot results, 14 -17 respectively, for PBSD and PEAD.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy between the shear thinning behavior of the aliphatic polyesters and that of the ethylene copolymers comes from the fact that longchain branches were formed by the CGCT catalyzed copolymerization of ethylene and 1-octene with the in situ-produced vinyl terminated polyethylene, due to the chain termination by ␤-hydride elimination and/or transfer to monomers, because long-chain branched polymers have higher shear sensitivity compared to the linear counterparts. Wang et al 13 observed long-chain branches up to 0.44/10,000 carbons were formed during ethylene homopolymerization with CGCT in a continuous stirred-tank reactor operating at 35 atm and 140 -190°C. Figure 6 are cole-cole plot results, 14 -17 respectively, for PBSD and PEAD.…”
Section: Resultsmentioning
confidence: 99%
“…elimination), k fM (transfer to monomer), and k fH (transfer to hydrogen). [12] The ratio between saturated and unsaturated chain ends is an important parameter for the study of chain transfer in the polymerization. [13] For PP systems, 13 C NMR analysis is also capable of revealing the stereo environment at the branching point.…”
Section: Nmrmentioning
confidence: 99%
“…A period of 20 hours at 75.4 MHz with a delay time of 10 s between pulses and more than 7000 scans was reported in Wang's work, to obtain 13 C NMR spectra with an acceptable resolution and signal-to-noise ratio. [12] To double the signal to noise ratio, the number of scans must be quadrupled, which dramatically increases to the acquisition time. A result of this is that an acquisition time of 1-46 days is required to obtain an accurate estimate of LCBD in the range of 0.2-1.0 branches per 10 000 carbons using high field solutionstate NMR (600 MHz, 1 H resonance).…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
See 1 more Smart Citation
“…The copolymerization of St and SIPM proceeded readily by titanium compounds-MAO catalysts giving powdered products in high yields, although catalytic activity was sensitive to the titanocene compounds examined. The structure of MEK-insoluble fraction of the graft copolymer was confirmed by 13 C and 1 H NMR spectroscopy to be the graft copolymer having a high syndiotacticity of the main chain and well-defined polyisoprene of the side chain as described previously. 34 From Table II, the electron-withdrawing chloro ligands of the half metallocene are favorable to produce syndiotactic polymers.…”
Section: Copolymerization Of Stand the Sipmmentioning
confidence: 70%